THE ROLE OF POSITIVE EMOTIONS AS A MEDIATION BETWEEN LIVE STREAMING AND FLASH SALES ON IMPULSE BUYING IN TIKTOK SHOP - Supiani; Asih Mauizah (International Journal Management and Economic, 2026)
The rise of social commerce platforms such as TikTok Shop reflects the integration of entertainment social interaction, and commerce. Features like Live Streaming and Flash Sale are widely recognized for shaping interactive shopping experiences that can trigger Impulsive Buying, particularly among Generation Z, who are highly engaged with digital media. This study explores the direct and indirect effects of Live Streaming and Flash Sale on Impulsive Buying, with Positive Emotion as a mediating variable. A quantitative approach was employed through an online survey of 200 Generation Z respondents in Greater Jakarta, analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Results show that Live Streaming and Flash Sale significantly influence Impulsive Buying, both directly and indirectly through Positive Emotion. The findings highlight the mediating role of emotional factors in digital marketing strategies and suggest that emotionally engaging, video-based shopping experiences can strengthen consumer involvement and enhance sales performance.